Pelatihan Pemanfaatan Artificial Intelligence untuk Pengembangan Multimedia Interaktif Guru IPA Kabupaten Takalar - Ahmad Zuhudy Bahtiar; Syarful Annam; Rifda Nur Hikmahwati Arif; Hasanuddin Hasanuddin (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2026)
The development of Artificial Intelligence (AI) has opened new opportunities in the development of more interactive and adaptive learning media. However, teacher competence in utilizing AI technology for developing learning multimedia is still relatively limited. This community service activity aims to improve the competence of science teachers in Takalar Regency in utilizing Canva AI Code and ChatGPT to develop interactive multimedia. The activity was carried out through seminars, training, direct practice, and mentoring methods. The activity participants were 30 teachers who are members of the Takalar Regency Science MGMP. The evaluation was conducted using a Likert-scale pretest and posttest instrument which was analyzed descriptively and inferentially using N-Gain and Paired Sample t-Test. The results of the activity showed that the average score of participants increased from 3.70 to 4.54, an increase of 16.73%. The results of the Paired Sample t-Test showed a significant difference between the pretest and posttest scores (p < 0.05). The N-Gain value of 0.64 is in the moderate category. These findings indicate that the Canva AI Code and ChatGPT training is effective in improving science teachers' competencies in developing AI-based interactive multimedia. This activity provides teachers with practical alternative solutions to produce more innovative, engaging, and 21st-century learning media.